2021
DOI: 10.1161/circulationaha.120.052358
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factor Trajectories Since Childhood and Cognitive Performance in Midlife: The Cardiovascular Risk in Young Finns Study

Abstract: Background: Cardiovascular risk factors, such as high blood pressure, adverse serum lipids, and elevated body mass index in midlife, may harm cognitive performance. It is important to note that longitudinal accumulation of cardiovascular risk factors since childhood may be associated with cognitive performance already since childhood, but the previous evidence is scarce. We studied the associations of cardiovascular risk factors from childhood to midlife, their accumulation, and midlife cognitive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…42 Therefore, assessment of CVD profiles, rather than single risk factors, is encouraged to capture a comprehensive state of CVD-related dementia risk. 17,23,24 FRS values are elevated by aging alone; hence, active suppression of the modifiable variables of the FRS (i.e., reduction of blood pressure or body mass index or smoking cessation) would have to take place to maintain a stable CVD risk trajectory. Furthermore, because the cross-sectional FRS values offered less predictive utility for survival or dementia outcomes, it is suggested that the relative accrual of multiple risk factors plays a larger part in determining outcome than standalone measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Therefore, assessment of CVD profiles, rather than single risk factors, is encouraged to capture a comprehensive state of CVD-related dementia risk. 17,23,24 FRS values are elevated by aging alone; hence, active suppression of the modifiable variables of the FRS (i.e., reduction of blood pressure or body mass index or smoking cessation) would have to take place to maintain a stable CVD risk trajectory. Furthermore, because the cross-sectional FRS values offered less predictive utility for survival or dementia outcomes, it is suggested that the relative accrual of multiple risk factors plays a larger part in determining outcome than standalone measurements.…”
Section: Discussionmentioning
confidence: 99%
“… 42 Therefore, assessment of CVD profiles, rather than single risk factors, is encouraged to capture a comprehensive state of CVD-related dementia risk. 17 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…The Pittsburg Sleep Quality Index was used to assess sleep quality, which is a risk factor for developing cardiovascular disease [ 39 , 40 ]. A large set of neuropsychological tests developed by the CANTAB (Cambridge Neuropsychological Test Automated Battery) research suite (Cambridge Cognition ® ; , accessed on 15 March 2022) [ 41 ] were also performed in Ghent, Lille, and Rome. These tests assess different cognitive functions such as attention, reaction time, memory, and executive function.…”
Section: Methodsmentioning
confidence: 99%
“…A 31-year follow-up study evidenced a direct correlation between cardiovascular risk factors and obesity in childhood with cognitive impairment in adulthood. The longitudinal increase in systolic blood pressure, total cholesterol and body weight was associated with worse cognitive scores in midlife, described as alterations in episodic memory, associative learning and sustained attention (Hakala et al, 2021). Bauer and colleagues reported that overweight and obesity in children reduced hippocampal volume and impaired executive cognitive performance (Bauer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%